Climate Change, Environmental Pollution and Covid-19 Pandemic The Triangle Impacts on Mental Health - Nazatul Faizah, Haron; Noraina Mazuin, Sapuan; Kumaran, Vikniswari Vija; Nur Surayya, Saudi; Abdul Rahim, Ridzuan (Macrothink Institute, 2022)
Converging data have recently received attention due to the linkages between environmental pollution, the COVID-19 pandemic, climate change, as well as mental health. This encourages explored the intricate interplay between climate change, environmental pollution, and the Covid-19 pandemic, shedding light on their collective impacts on global mental health. The empirical evidence presented reveals how climate-induced disasters and pollution exacerbate mental health challenges, while the pandemic's multifaceted effects further compound these burdens. Vulnerable populations, including low-income communities, children, and frontline workers, face disproportionate mental health implications in this context. As the implications of this "triangle impact" become increasingly evident, urgent and comprehensive action is imperative. Policymakers and healthcare practitioners must adopt an integrated approach that incorporates climate adaptation measures, pollution mitigation strategies, and pandemic preparedness efforts to address these complex challenges. Equitable access to mental health services is crucial, recognizing mental well-being as a cornerstone of overall resilience. By fostering collaborative and empathetic action, society can forge a path toward a sustainable and mentally healthy future for all.